A rare form of discoid lupus erythematosus as a rosacea and angiofibroma: A case report. Issue 1 (19th December 2019) - Mokhtari, Fatemeh; Ganjei, Zakiye
Abstract: The rare presentation of DLE can be rosacea‐/angiofibroma‐like lesions which should be considered in patients with red‐pink to skin‐color papules with flushing and photosensitivity. Abstract : The rare presentation of DLE can be rosacea‐/angiofibroma‐like lesions which should be considered in patients with red‐pink to skin‐color papules with flushing and photosensitivity.